Clinical and in vitro evidence for the antimicrobial therapy in Burkholderia cepacia complex infections. Issue 5 (May 2015) - Gautam, Vikas; Shafiq, Nusrat; Singh, Meenu; Ray, Pallab; Singhal, Lipika; Jaiswal, Nishant P; Prasad, Amber; Singh, Shaunik; Agarwal, Amit
<x xml:space="preserve">Abstract</x> Treatment of infections caused by Burkholderia cepacia complex (Bcc) in cystic fibrosis (CF) patients poses a complex problem. Bcc is multidrug-resistant due to innate and acquired mechanisms of resistance. As CF patients receive multiple courses of antibiotics, susceptibility patterns of strains from CF patients may differ from those noted in strains from non-CF patients. Thus, there was a need for assessing in vitro and clinical data to guide antimicrobial therapy in these patients. A systematic search of literature, followed by extraction and analysis of available information from human and in vitro studies was done. The results of the analysis are used to address various aspects like use of antimicrobials for pulmonary and non-pulmonary infections, use of combination versus monotherapy, early eradication, duration of therapy, route of administration, management of biofilms, development of resistance during therapy, pharmacokinetics–pharmacodynamics correlations, therapy in post-transplant patients and newer drugs in Bcc-infected CF patients.